The discovery of “sale amarissimo antifebbrile” (“bitter febrifugal saline”) by Bartolommeo Rigatelli, i.e. the origins of pharmacoeconomics - Marson, Piero; Pasero, Giampiero (Farmeconomia. Health Economics and Therapeutic Pathways, 2008)
When considering the history of salycilates, it has to be underlined that a number of Italian scientists made significant contributions on such a topic. Among these, two pharmacists, Bartolommeo Rigatelli in Verona and Francesco Fontana in Lazise, carried out the first extraction of the active component of willow bark in 1824. Rigatelli named the drug “sale amarissimo antifebbrile” (“bitter febrifugal saline”). In his report some references of pharmacoeconomics are sketched out, thus indicating the attention that the Austrian government on the North Italian districts gave to the management policy. In fact, Rigatelli carried out an economic account of the use of salicin extracts as an antipyretic agent instead of the chincona bark which had been imported from South America at that time and was very expensive. This historical report gives rise to outline a brief history of pharmacoeconomics.